2010
DOI: 10.1074/jbc.m109.089078
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Maltose Transport System Reveal a Mechanism for Coupling ATP Hydrolysis to Substrate Translocation without Direct Recognition of Substrate

Abstract: The ATPase activity of the maltose transporter (MalFGK 2 ) is dependent on interactions with the maltose-binding protein (MBP). To determine whether direct interactions between the translocated sugar and MalFGK 2 are important for the regulation of ATP hydrolysis, we used an MBP mutant (sMBP) that is able to bind either maltose or sucrose. We observed that maltose-and sucrose-bound sMBP stimulate equal levels of MalFGK 2 ATPase activity. Therefore, the ATPase activity of MalFGK 2 is coupled to translocation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The predominant solution scattering shape of MBP was restored by averaging 10 individual dummy residue models derived from the SAXS data of MBP at a protein concentration of 0.7 mg/ml (data not shown). Interestingly, manual placement of the crystal structure of MBP (PDB code 3HPI, chain A) showed a good fit with the SAXS-derived envelope volume (32). This confirmed that MBP predominantly exists as monomer in solution and the dimeric state of HAMP1-5 MBP was driven intrinsically.…”
Section: Size Exclusion Chromatography-malls Experiments Hamp1-5 Mbpsupporting
confidence: 50%
“…The predominant solution scattering shape of MBP was restored by averaging 10 individual dummy residue models derived from the SAXS data of MBP at a protein concentration of 0.7 mg/ml (data not shown). Interestingly, manual placement of the crystal structure of MBP (PDB code 3HPI, chain A) showed a good fit with the SAXS-derived envelope volume (32). This confirmed that MBP predominantly exists as monomer in solution and the dimeric state of HAMP1-5 MBP was driven intrinsically.…”
Section: Size Exclusion Chromatography-malls Experiments Hamp1-5 Mbpsupporting
confidence: 50%
“…Extra density attributed to MBP on Mcm6 and Mcm3 is colored orange or light blue, respectively; only a portion of the Mcm4 tail is observable in the full-length constructs and is highlighted in green. ( h ) Density corresponding to MBP on Mcm3 (light blue) or Mcm6 (orange), cut out from the CMG density maps and compared to the density map calculated from the MBP crystal structure, PDB entry 3HPI 51 , filtered to 30 Å and showed at 5σ (gray).…”
Section: Figurementioning
confidence: 99%
“…Two laboratories have tested whether direct binding of maltose to MalFGK 2 is required for ATP hydrolysis. Shilton and colleagues designed a MBP mutant that binds both maltose and sucrose [16]. Genetic studies have shown that sucrose is a poor competitor for the maltose-binding site in MalFGK 2 , suggesting that the maltose-binding site in MalFGK 2 does not recognize sucrose [17,18].…”
Section: How Does Substrate Activate Atpase Activity?mentioning
confidence: 99%
“…Genetic studies have shown that sucrose is a poor competitor for the maltose-binding site in MalFGK 2 , suggesting that the maltose-binding site in MalFGK 2 does not recognize sucrose [17,18]. However, the mutant MBP stimulated the ATP hydrolysis equally well with maltose or sucrose, indicating that the closed conformation of MBP is sufficient to initiate the transport cycle [16]. Davidson and colleagues substituted an aspartate for glycine in the maltose-binding site to prevent maltose binding to MalFGK2.…”
Section: How Does Substrate Activate Atpase Activity?mentioning
confidence: 99%